Secondary Plasma Cell Leukemia: A Case Report - Swaminathan, Neeraja (Cureus, 2020)
Plasma cell leukemia (PCL) is a rare and aggressive variant of myeloma and has a poor prognosis. It needs prompt recognition in order to institute timely treatment. Given its relatively low incidence, it is an evolving area of research as well. This case report describes a patient with PCL in the setting of a previously treated myeloma. The report also reviews the clinicopathologic, cytogenetic, and immunophenotypic characteristics of PCL and its management.